Safety and Tolerability of Vitamin D Supplementation in the Vitamin D and Type 2 Diabetes (D2d) Study – A Randomized Trial in Persons With Prediabetes. (7th June 2021) - Johnson, Karen; Pittas, Anastassios; Margolis, Karen; Peters, Anne; Phillips, Lawrence; Vickery, Ellen; Nelson, Jason; Sheehan, Patricia; Reboussin, David; Malozowski, Saul; Chatterjee, Ranee
Abstract: Objectives: The routine use of vitamin D supplements has increased substantially in the United States. However, the safety and tolerability of long-term use of high-dose vitamin D are unknown. We assessed the safety and tolerability of vitamin D3 at a dose of 4000 IU daily in the vitamin D and type 2 diabetes (D2d) trial. Methods: Persons with overweight/obesity and prediabetes without a recent history of nephrolithiasis, hypercalcemia, hypercalciuria, or other conditions potentially associated with vitamin D use, were randomized to either daily 4000 IU of vitamin D3 or placebo. Participants were allowed to take vitamin D up to 1000 IU/day and calcium up to 600 mg/day, in addition to study medication. Incident adverse events (AE), defined as any untoward or unfavorable medical occurrence, were ascertained in both groups at in-person visits and interim phone or email encounters four times a year. Serious AEs (SAE) were defined as those AEs that resulted in death, new or prolonged hospitalization, persistent or significant disability, or congenital anomaly or birth defect, or were life threatening or represented another significant hazard. Results: A total of 8, 304 AEs occurred during three years of follow-up. AEs were less frequent in the vitamin D group compared to placebo [4039 (116.1 events per 100 person-years) vs. 4265 (123.8 events per 100 person-years) (Incidence Rate Ratio [IRR] = 0.94; 95% Confidence Interval (CI) 0.90, 0.98)]. The overall frequency of protocol-specified AEs of interest was low, including nephrolithiasis, hypercalcemia, hypercalciuria, and low estimated glomerular filtration rate (eGFR) with no significant between-group differences. There were also no significant differences between the vitamin D and placebo groups in SAEs (IRR = 0.95; 95% CI 0.81, 1.13). Conclusions: Vitamin D3 supplementation at 4, 000 IU per day was safe and well-tolerated and did not increase risk of AEs or SAEs, including those typically associated with vitamin D excess such as hypercalciuria or nephrolithiasis. Funding Sources: National Institute of Diabetes and Digestive and Kidney Diseases, Office of Dietary Supplements of the National Institutes of Health, the American Diabetes Association.